Motivational aspects that influence the elderly to enroll on and continue participating in physical exercise programs - Carmen Freyre; Ana Carolina Leão; Clara Maria Silvestre Monteiro de Freitas; Marcela de Souza Santiago; Ana Tereza Viana (Universidade Federal de Santa Catarina, 2007)
Currently, there is a growing demand for physical exercise in programs promoting health; however, the elderly are still under-represented in such programs. This study aims to identify, classify and discuss social, cultural and educational factors relating to the health and quality of life of the elderly, establishing relationships with the motives for which they join and adhere to regular physical exercise programs in public areas. This was a field study employing descriptive quantitative and qualitative methodology and for which 120 participants from two physical exercise programs in Recife were interviewed. The results indicate that the most important motives for participation were as follows: to improve health (84.2%), to improve physical performance (70.8%), to adopt a healthy lifestyle (62.5%), to reduce stress (60.8%), to comply with doctor's orders (56.7%), to recover from injury (55%), to improve self-image (50.8%) and to enhance self-esteem and relax (47.5%). The most important motives for continuing to attend such programs were: to improve posture (75%); to promote a feeling of wellbeing (74.2%); to keep fi t (70.8%); to experience pleasure (66.7%); to become stronger and be motivated by the instructor (62.5%); to experience a feeling of well-being produced by the social environment (60%); and to experience self-realization and receive attention from the instructor (57.5%). For the men (35.1%), the habit of performing physical exercise in their youth had no bearing on their joining such programs. On the basis of these indicators, universities can make a valuable contribution by offering socio-educational health-related projects encouraging the elderly population to avoid a sedentary lifestyle. RESUMO Atualmente, a busca pela prática de exercícios físicos em programas para promoção de saúde vem crescendo; porém a procura pelos idosos é insuficiente. Esta investigação identifica, classifica e discute os aspectos socioculturais e educativos ligados à saúde e a qualidade de vida do idoso, estabelecendo relações com os motivos de adesão e permanência, na prática regular de exercícios físicos, realizados em espaços públicos. A metodologia foi descritiva quantiqualitativa de campo com o auxílio da qual foram entrevistados 120 usuários de dois programas de exercícios físicos no Recife. Os resultados apontaram os motivos mais importantes para adesão: melhorar a saúde (84,2%); melhorar o desempenho físico (70,8%); adotar estilo de vida saudável (62,5%); reduzir o estresse (60,8%); acatar prescrição médica (56,7%); auxiliar na recuperação de lesões (55%); melhorar a auto-imagem (50,8%); melhorar a auto-estima e relaxar (47,5%). Elencam-se os motivos mais importantes para a permanência: melhorar a postura (75%); promover o bem-estar (74,2%); manter-se em forma (70,8%); sentir prazer (66,7%); fi car mais forte e receber Incentivos do professor (62,5%); sentir bem-estar provocado pelo ambiente (60%); sentir-se realizado e receber atenção do professor (57,5%). Para os homens (35,1%), o hábito de praticar exercícios na juventude não revelou importância para aderir à prática de exercícios. Com esses indicadores, promover programas voltados à promoção da saúde e das necessidades dos idosos fará jus a uma população que tem motivos sufi cientes para sair do sedentarismo.